2014
DOI: 10.1044/2014_jslhr-s-13-0094
|View full text |Cite
|
Sign up to set email alerts
|

Webcam Delivery of the Lidcombe Program for Early Stuttering: A Phase I Clinical Trial

Abstract: Webcam-delivered Lidcombe Program intervention is potentially efficacious, is practical and viable, and requires further exploration with comparative clinical trials and a qualitative study of parent and caregiver experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 20 publications
2
57
0
Order By: Relevance
“…Telehealth in speech-language pathology is becoming an established practice in certain areas, with research indicating successful use in treating fluency disorders (Harrison et al, 1999;Lewis, Packman, Onslow, Simpson, & Jones, 2008;O'Brian, Smith, & Onslow, 2014;Wilson, Onslow, & Lincoln, 2004), dysphagia (Sharma, Ward, Burns, Theodoros, & Russell, 2013;, adult speech and language disorders (Constantinescu et al, 2010;McGrath, Dowds, & Goldstein, 2008) and speech sound disorders in childhood (Grogan-Johnson et al, 2013). Telehealth has also been used successfully in formal language assessments in children (Sutherland et al, 2017;Waite, Theodoros, Russell, & Cahill, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Telehealth in speech-language pathology is becoming an established practice in certain areas, with research indicating successful use in treating fluency disorders (Harrison et al, 1999;Lewis, Packman, Onslow, Simpson, & Jones, 2008;O'Brian, Smith, & Onslow, 2014;Wilson, Onslow, & Lincoln, 2004), dysphagia (Sharma, Ward, Burns, Theodoros, & Russell, 2013;, adult speech and language disorders (Constantinescu et al, 2010;McGrath, Dowds, & Goldstein, 2008) and speech sound disorders in childhood (Grogan-Johnson et al, 2013). Telehealth has also been used successfully in formal language assessments in children (Sutherland et al, 2017;Waite, Theodoros, Russell, & Cahill, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…), stuttering therapy (O'Brian et al . , Bridgman et al . ), and assessment and intervention for speech‐sound disorders, including childhood apraxia of speech (Grogan‐Johnson et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the Australian context, a 2014 Senate inquiry found that not only were there fewer speech-language pathologists (SLPs) working outside urban areas, but also the ratio of therapists per 100 000 people declined as rurality increased (Community Affairs References Committee 2014). Telehealth is one way of addressing some of the barriers associated with staffing and access issues and it has been shown to be an acceptable and viable alternative to face-to-face speech-language services in a range of specialties, including dysphagia assessment and intervention (Collins et al 2017, Sharma et al 2013, stuttering therapy (O'Brian et al 2014, Bridgman et al 2016, and assessment and intervention for speech-sound disorders, including childhood apraxia of speech (Grogan-Johnson et al 2013, Thomas et al 2016, Waite et al 2012. Telehealth has also been used to provide formal assessments of child language with young children with no known language difficulties (Waite et al 2010), as well as children with reading difficulties (Sutherland et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatment via video conferencing has been demonstrated for the Lidcombe Program for stuttering (O'Brian et al . ), the Camperdown Program for stuttering (Carey et al . ), and the Lee Silverman Voice Treatment (LSVT ® ) for patients with Parkinson's disease (Constantinescu et al .…”
Section: Introductionmentioning
confidence: 99%